(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This article describes some relationships established among faithful, priests and government employees, into the parishes of Mexico State archbishopric during President Sebastián Lerdo de Tejada´s term. Being the Church-State links very harsh on the villages scale, it´s remarkable the setting of very efficient networks formed by these social actors, in order to minimise or nullify the enforcement of Reform Laws. Archbishop Pelagio Antonio de Labastida combines prudence with astuteness, preventing of serious conflicts.